Cost-effectiveness of complex cardiac rehabilitation of patients with ischemic heart disease, complicated with with heart failure, comorbid with type 2 diabetes mellitus - M. N. Sinkova; L. K. Isakov; E. Yu. Plotnikova; M. A. Sinkov (Лечащий Врач)
The limited amount of financing of the budget and insurance of health care system necessitates the introduction of special techniques into practical health care, aimed at rationalizing therapeutic measures. The study showed the economic efficiency of complex cardiac rehabilitation at all stages of rehabilitation treatment of patients with chronic heart falure, on the background of type 2 diabetes mellitus.